Pembentukan Akhlak Siswa SDIT Muhammadiyah Wirosari Dimasa Pandemi 2020 - Rohman, Abdullah Kiddatul Rohman; Narimo, Sabar; Ali, Mohammad (FKIP, PGSD, Universitas Slamet Riyadi, 2023)
The purpose of this study was to identify and describe the strategy of moral formation of SDIT Muhammadiyah Wirosari students during the 2020 pandemic. The study used a field research method with a descriptive qualitative approach. While the subjects of this study consisted of the principal, waka curriculum, waka student, Islamic education teachers and classroom teachers. Data was collected by means of observation, interviews, and documentation. The results of this study are: 1) the limited interaction between teachers and students becomes a separate obstacle for educators and schools, 2) the lack of supervision from people results in student activities being less well supervised, 3) poor service because there are still some students who are not have adequate facilities.